Strength and durability of self consolidating concrete containing recycled materials / Mohd Afiq Mohd Fauzi ... [et al.] - Mohd Fauzi, Mohd Afiq; Mohd Ridzuan, Ahmad Ruslan; Arshad, Mohd Fadzil; Jasmi, Nurliza; Harun, Mohd Shafee; Shahidan, Shahiron (2018)
Self-Consolidating Concrete (SCC) is developing class of concrete materials that offers great potential to improved ease of positioning and cost through reduced time and labor. Generally, amount of Construction and Demolition Wastes (C&DW) are increased daily. Therefore, it is beneficial to final usage of coarse recycled concrete aggregate that produced from crushed concrete waste as a new construction solution. Researchers have found that waste materials have unique properties that could help in improving the quality of self-consolidating concrete produced. Therefore, reuse of RCA generated as the supplemental material for the replacement of aggregate are significant in reducing the environmental impact. This research was focused on the strength characteristic and the chloride permeability level of SCC containing RCA. The influence of RCA content in the range from 0% to 100% of Natural Aggregate (NA) to the strength characteristic and the chloride permeability level of SCC was identified and compared with SCC containing normal mixes. In this research, three (3) series of concrete specimens were cast with different water cement ratios (0.53, 0.49 and 0.45). The concrete specimens were subjected to strength at the age of 3, 7, 14, 21, 28, 56 and 90 days and durability at the age of 28, 56 and 90 days. The result shown that the compressive strength and chloride permeability of SCC containing 100% RCA replacement give better performance than the 0% RCA replacement. Based on the finding, SCC containing 100% RCA replacement can be categorized similar to conventional concrete hence it can be utilized for construction purposes. RCA can also acts as an alternative replacement in concrete for replacing the NA.